2011
DOI: 10.1111/j.1540-6288.2010.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Oil Risk Exposure: The Case of the U.S. Oil and Gas Sector

Abstract: We estimate oil price risk exposures of the U.S. oil and gas sector using the FamaFrench-Carhart's four-factor asset pricing model augmented with oil price and interest rate factors. Results show that the market, book-to-market, and size factors, as well as momentum characteristics of stocks and changes in oil prices are significant determinants of returns for the sector. Oil price risk exposures of U.S. oil and gas companies in the oil and gas sector are generally positive and significant. Our study also find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 64 publications
15
67
0
Order By: Relevance
“…Sadorsky (2001) and Boyer and Filion (2007) find a positive significant relationship between oil price shocks stocks returns for Canadian oil and gas companies, El-Sharif et al (2005) report the same result for UK oil and gas companies as does Mohanty and Nandha (2011) for US oil and gas companies. Dayanandan and Donker (2011) report that oil price increases have a positive and statistically significant impact on the accounting profits of oil and gas companies in North America.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Sadorsky (2001) and Boyer and Filion (2007) find a positive significant relationship between oil price shocks stocks returns for Canadian oil and gas companies, El-Sharif et al (2005) report the same result for UK oil and gas companies as does Mohanty and Nandha (2011) for US oil and gas companies. Dayanandan and Donker (2011) report that oil price increases have a positive and statistically significant impact on the accounting profits of oil and gas companies in North America.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Several other studies have found the expected positive relationship between oil prices and the stock market returns of oil and gas companies [8] [9]. There is further evidence of variation in returns across industry subsectors [8], although some early studies found no significant effects [10] [11].…”
Section: Literature Reviewmentioning
confidence: 90%
“…However, studies rarely assessed the impact at the sector or sub-sector level, though Mohanty and Nandha [8] and Hommoudeh and Li [7], are exceptions. Moreover, those who look at individual firms or sectors focus almost exclusively on the oil-producing sector 2 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fourthly, there is no clear evidence that using book to market ratio can be a successful strategy in the oil and gas sector. Fifthly, the formation of portfolios based on momentum will not be a useful strategy in the oil and gas Faff and Brailsford (1999), Nandha (2011) andBroadstock et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the findings of Faff and Brailsford (1999), Mohanty et al (2010) found no significant relationship between oil prices and stock returns over the period of the study between 1998 and 2010. Mohanty and Nandha (2011) estimated the oil price risk exposure of the US oil and gas sector using Fama-French-Carhart's four factor asset pricing model. The model was expanded by an additional risk factor of the monthly changes in oil price using West Texas Intermediate (WTI).…”
Section: Review Of Literaturementioning
confidence: 99%